A Unique Architecture Based on 1 D Semiconductor, Reduced Graphene Oxide, and Chalcogenide with Multifunctional Properties. Issue 33 (25th July 2014) - Mukherjee, Bratindranath; Gupta, Satyajit; Peterson, Aaron; Imahori, Hiroshi; Manivannan, Ayyakkannu; Subramanian, Vaidyanathan (Ravi)
Abstract A unique heterostructured optoelectronic material (HOM), consisting of a reduced graphene oxide (RGO) layer with spatially distributed CdS, suspended by zinc oxide (ZnO) nanorods, is presented. The key features of this HOM are the assembly of the components in a manner so as to realize an effective integration between the constituents and the ability to modify the electronic properties of the RGO. For the first time, the location of RGO (as a suspended layer) along with the tuning of its charge‐transport properties (n‐/p‐type) and its influence on the photo(electro)chemical processes has been examined systematically by using this ZnO/RGO/CdS HOM as a case study. The n‐type RGO interlayer facilitates >100 % increase in the photocurrent density and 25 % increase in the photodegradation of a dye, compared to ZnO/CdS, thus demonstrating its multifunctionality. At 3.2 mA cm−2, this HOM architecture helps to achieve the highest photocurrent density utilizing ZnO, RGO, and CdS as building blocks in any form. The work is significant for the following reasons: i) other one dimensional (1D) oxides/chalcogenides or 1D oxides/dyes may be designed with similar architectures; ii) HOMs with tunable optical absorbance and charge‐transport properties could be realized; iii) related application areas (e.g., sensing or solar fuel generation) should be greatly benefited.